Feedback in field experiences: interactions between university supervisors and student teachers - Flores Gómez, Catherine (2022)
Introduction: The research sougth to identify the type the interventions produced between university supervisors and student teachers during feeback phase in practical training. Objetive: To analyse how interactions can promote reflection and autonomy of teacher in training. Method: Methodologically trained in a case stady two supervisors and ten student teachers from public university in the Chile participated. They were examined ten transcripts of video recordings were analyzed using Heron´s interpersonal relationships analysis framework for the description of feedback given by the supervisors. Results: The main findings accounts for two interventions areas in which the dialogue is centered: feeback focused on management skills and classroom procedures and predominantly directive feedback with the presence of non-directive interventions focused in giving support.